Prospective single center trial of next-generation sequencing analysis in metastatic renal cell cancer: the MORE-TRIAL - Dieffenbacher, Svenja; Zschäbitz, Stefanie; Hofer, Luisa; Hatiboglu, Gencay; Hou, Weibin; Hohenfellner, Markus; Duensing, Stefan; Sültmann, Holger; Pahernik, Sascha; Grüllich, Carsten (Future Science OA, 2018)
Aim: Targeted therapies have substantially improved the survival of patients with metastatic clear cell renal cell cancer. No prognostic or predictive biomarkers are available. Comprehensive genetic profiling offers the opportunity to define prognostic and predictive signatures aiming at a more personalized approach to treatment. Methods: In this prospectively conducted cohort study, tumor tissue and liquid biopsies are sampled at baseline and upon first and second progression under systemic treatment. Samples will be analyzed by whole-exome sequencing to generate prognostic and predictive patterns for systemic therapies. Discussion: This study is aiming at exploring genetic profiles with prognostic and predictive value in metastatic renal cell cancer patients. Clonal evolution facilitating resistance to systemic treatment will be investigated by repeat biopsies.
Gesehen am 03.03.2020